Interpretation of the "Student Engagement" paradigm in Spain (a bibliometric review) - Elena Catalán Martínez; Gloria Aparicio de Castro (Centro de Estudios Financieros, 2017)
In this paper, we aim to evaluate the impact and the interpretation that has been made of the concept of «Student Engagement» in the Spanish university system. For this purpose, we have reviewed the contributions made in the last five years to the main international congresses on university teaching innovation held in Spain and the national-level publications on this topic that are registered in the Scopus and Web of Science databases. Through this review, we can determine not only the impact of Student Engagement among national and international teachers that participate in these forums, but also the interpretation they make of the concept. The review of the documents, and our own position as teachers, makes us reflect on a proposal that could guide future lines of research on the issue. In this regard, we consider that the management of the university, especially in the Spanish system, still does not take a holistic perspective of the university student's experience into account. In order to fully develop the three dimensions of action to improve Student Engagement, we need a multidisciplinary approach that would take into consideration the purest contributions from management, from university experiential marketing, and from the educational sciences with their knowledge of teaching methodologies.